2020
DOI: 10.1186/s13031-019-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

The refugee post-migration stress scale (RPMS) – development and validation among refugees from Syria recently resettled in Sweden

Abstract: Background: Despite the growing recognition of the impact of post-resettlement factors on the mental health of refugees, a clear definition of the concept of post-migration stress, as well as an updated, valid instrument for assessing the construct, are still lacking. The aim of the current study was to develop and validate the Refugee Post-Migration Stress Scale (RPMS), a concise, multi-dimensional instrument for assessing post-migration stress among refugees. Results: Based on a review of previous research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 60 publications
2
69
0
5
Order By: Relevance
“…Three subscales of the Refugee Post-Migration Stress Scale (RPMS) [ 14 ] were used to measure the construct of social and financial hardship based on asylum seekers’ responses to: (1) experiencing perceived discrimination ; (2) material and economic strain ; and (3) social strain while living in housing facilities in Sweden. RPMS is a concise, multidimensional self-assessment instrument for the evaluation of post-migration stress among refugees based on a theoretical conceptualization and empirical evidence of the construct of post-migration stress.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three subscales of the Refugee Post-Migration Stress Scale (RPMS) [ 14 ] were used to measure the construct of social and financial hardship based on asylum seekers’ responses to: (1) experiencing perceived discrimination ; (2) material and economic strain ; and (3) social strain while living in housing facilities in Sweden. RPMS is a concise, multidimensional self-assessment instrument for the evaluation of post-migration stress among refugees based on a theoretical conceptualization and empirical evidence of the construct of post-migration stress.…”
Section: Methodsmentioning
confidence: 99%
“…Social and financial hardship was first modelled as three correlated first-order latent variables using the subscales of the RPMS perceived discrimination (four items), material and economic strain (four items), and social strain (three items) on the basis of the previously suggested factorial structure of the RPMS [ 14 ]. Next, a modeled second order “umbrella” latent variable of social and financial hardship was examined with these three latent variables as indicators (see Supplementary Material ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A vast amount of migration studies have explored perceived stress in the process or as an effect of moving countries. In particular, [42] verified following domains of post-migration stress: perceived discrimination, lack of host country specific competences, material and economic strain, loss of home country, family and home country concerns, social strain, and family conflicts. Another research has elaborated on the consequences of international migration on the example of Polish migrant workers in Scotland [43].…”
Section: Perceived Stress and Its Outcomesmentioning
confidence: 92%
“…A qualitative interview conducted with 68 Syrian refugees in the North of Jordan revealed that emotional distress is a central concern and is frequently highlighted as the trigger for a non‐communicable disease or its exacerbation (McNatt et al., 2019). Stress among refugees could come from perceived discrimination, lack of support from host country, lack of materials, missing home country, concerns about family in home country, economic and social strain and family conflicts (Malm, Tinghög, Narusyte, & Saboonchi, 2020). There is a need to identify whether Syrian refugees use stress management to protect their health.…”
Section: Introductionmentioning
confidence: 99%